2015
DOI: 10.1177/2150135114563938
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Tumors

Abstract: Abstract:Background: Cardiac tumors in children are rare. Of cases reported in the literature, nearly all are benign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Cardiac tumors are rare in children with an incidence of 0.17–0.2% [ 8 , 9 ]. The most common pediatric cardiac tumors are rhabdomyomas [ 1 , 4 , 5 , 10 12 ], 10% of which are familial and associated with Carney complex [ 6 ]. Cardiac myxomas have been diagnosed more frequently with the advent of echocardiography [ 3 ] and are most commonly located in the left atrium [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac tumors are rare in children with an incidence of 0.17–0.2% [ 8 , 9 ]. The most common pediatric cardiac tumors are rhabdomyomas [ 1 , 4 , 5 , 10 12 ], 10% of which are familial and associated with Carney complex [ 6 ]. Cardiac myxomas have been diagnosed more frequently with the advent of echocardiography [ 3 ] and are most commonly located in the left atrium [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tumors are rare in the pediatric population, found in less than 0.5% of children evaluated for cardiac disease [ 1 ]. Atrial myxomas are the most common cardiac tumor in adults, most commonly presenting with cardiac symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genital rhabdomyoma is observed in young and middle-aged women. Cardiac rhabdomyomas occur chiefly, but not exclusively, in the pediatric age group; a 45-year single-institution review found rhabdomyoma to account for 58% of cardiac neoplasms in 64 pediatric patients (age <18 years) who presented for surgical evaluation of a cardiac tumor ( 12 ). Rhabdomyomatous mesenchymal hamartoma of the skin is observed in newborns and infants.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the risk of embolization or hemodynamic compromise, left side lesions, such as myxomas, should undergo resection. In the case of malignant cardiac tumors, surgical excision in combination with systemic chemotherapy remains the best available treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%